The Political Impetus behind the Construction of Anti-corruption Institutions in Developing Countries: An Analysis of the Process Leading up to India's Lokpal and Lokayuktas Act (LALA)*. (2nd July 2016) - Bina, Xiao; Yinghong, Huang
Abstract: Existing anti-corruption theories adopt "state-centric, " "market-centric" or "governance/ good governance" approaches as their dominant research direction. These theories are grounded in Western systems of liberty and democracy and their analysis is couched in terms of the logic of the division between public and private, which makes it difficult for their proponents to gain an insight into the unique experience of developing countries. The process behind India's Lokpal and Lokayuktas Act (LALA), starting from 2010, shows that developing countries may have another anti-corruption route: a composite tripartite anti-corruption model. In this model, the government, the elite and the mass of the people constitute the three main players in the anti-corruption drive. The three forms a complex multi-faceted relationship premised on compliance with bottom-line standards and the use of positive interaction in a dynamic balance that advances the construction of anti-corruption institutions. Summing up the experience and synthesizing the theory of this model will not only help us explore a new anti-corruption approach but will also stimulate our thinking about the unique state-society relationships of developing countries and the political impetus underlying their institutional construction.